PERBEDAAN KADAR ENDOTELIN-1 PADA PENDERITA DIABETES MELLITUS TIPE 2 WANITA DENGAN RETINOPATI ATAU NEFROPATI DIBANDINGKAN TANPA RETINOPATI DAN NEFROPATI - , SITI MUZAYYANAH; , dr. Luthfan Budi Purnomo, SpPD-KEMD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Chronic complications of diabetes mellitus (DM) include microangiopathy and macroangiopathy. Microangiopathy include retinopathy, nephropathy and neuropathy, while macroangiopathy include coronary heart disease, stroke and peripheral arterial disease. In type 2 diabetes mellitus (DM) when the diagnosis is established, approximately 25% had suffered nonproliferative diabetic retinopathy. Within 1-3 years of non proliferative retinopathy progress to proliferative diabetic retinopathy can eventually lead to retinal detachment, glaucoma and blindness. Diabetic nephropathy occurs in 20- 40% of patients with diabetes mellitus. Diabetic nephropathy is the leading cause of End Stage Renal Disease (ESRD) and is a high risk of Cardiovascular Disease (CVD). Endothelial dysfunction underlies all of this. Markers of endothelial endothelin-1 is assessed in patients with type 2 diabetes with retinopathy or nephropathy and without retinopathy and nephropathy. Aim. To evaluate the difference levels of endothelin-1 in type 2 diabetes mellitus women with retinopathy or nephropathy and without retinopathy and nephropathy. Methods. Cross sectional design was conducted on subjects from outpatients type 2 diabetes mellitus women with retinopathy or nephropathy compared without retinopathy and nephropathy at endocrinology clinic, Dr. Sardjito General Hospital, Yogyakarta. ELISA sandwichâs methods was used to measure plasma levels of endothelin-1 from veins blood. Differences between groups were compared by studentâs unpaired t-test and Mann-Whitney test ( significant when p<0.05). Diabetic retinopathy is enforced through inspection fundoskopi. Diabetic nephropathy is made by albumin creatinine ratio (ACR) â¥ 30ug/mg. Results. There are 52 female subjects with type 2 DM is composed of 26 (50%) subjects with retinopathy or nephropathy and 26 (50%) subjects without retinopathy and nephropathy. Median age was 54 (44-59) years. The mean levels of endothelin-1 obtained was higher in women with type-2 diabetes mellitus with retinopathy or nephropathy (19,47 Â± 9,94 ng / ml) compared with no retinopathy and nephropathy (17,64 Â± 11,63 ng / ml), although the difference was not statistically significant (p = 0,944). Conclusion. Endothelin-1 levels were higher in women with type-2 diabetes mellitus with retinopathy or nephropathy than without retinopathy and nephropathy, but the difference was not statistically significant.